Meningkatkan Softskill Wirausaha - Novitrisani, Yulinda; Maududi, Ahmad; Muthmainah, Badriyah; Febrieta, Ditta (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Entrepreneurship (entrepreneurship) is one of the most important sectors in a country's economy. Entrepreneurs not only play a role in creating jobs, but also in accelerating economic growth and innovation. In this competitive world of entrepreneurship, it is not enough just to have technical skills or hard skills, but also adequate soft skills. Soft skills refer to skills related to the ability to interact, communicate and adapt to an ever-changing social and professional environment. In this activity, the method used is a lecture or presentation with the aim of delivering material containing theories, concepts and the importance of mastering soft skills. in entrepreneurship to participants. With the presentation method, participants are given an understanding of the importance of creativity & optimism in building MSMEs, product promotion strategies, and the tools needed for MSMEs such as marketing platforms. The material is presented systematically using presentation slides, example images, and also presented using a whiteboard to facilitate explanation and understanding for participants. Mastery of soft skills can improve an entrepreneur's ability to face daily challenges. In this case, Gibb (2018) stated that soft skills greatly influence the success of an entrepreneur in facing market dynamics and ever-changing consumer needs. For example, good emotional intelligence can help entrepreneurs manage stress, communicate well in difficult situations, and make wise decisions (Luthans & Youssef, 2018). Presenting material regarding entrepreneurial soft skills is one part of community empowerment in navigating MSMEs in the digital era.